Guidelines for Organic Handling Requirements for Citrus Packinghouses and Processors - James J. Ferguson; Mark A. Ritenour (EDIS)
In 1990, Congress passed the Organic Foods Production Act, part of the 1990 Farm Bill, requiring the USDA to develop national standards for organically produced agricultural products. This was done to assure consumers that agricultural products marketed as organic meet consistent, uniform standards. After ten years of debate and discussion, the final rule of the National Organic Program (NOP) was published in the Federal Register in December, 2000 and fully implemented in October 21, 2002. This final rule codifies the National Organic Program and refers to specific regulations whereas the National Organic Program refers to the overall program established by the federal Organic Foods Production Act of 1990. This document is HS983, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.